ANALISIS PENGARUH PERILAKU INDUSTRITERHADAPNILAI PRODUKSI PADA INDUSTRI KECIL DI KOTA SINGKAWANG - B01111092, Nurma Darwati Darwati (Fakultas Ekonomi dan Bisnin Universitas Tanjungpura, 2015)
This reaserch is entitled an analysis of the influence of industrial behavior and the production value on small industries in Singkawang City. The research aimed to find out the influence of industrial behavior and production value on small industries in Singkawang as well as to compare between agribusiness and non-agribusiness industries. It was a quanitative descriptive study using the panel data regression model, as well as R Square test, F-test and t-test to test the hypothesis of whether the investment value and labor had an influence on the production value. The results indicated that in a small agribusiness industry, the investment value had a negative influence, while labor had positive influence on the production value. In small non-agribusiness industry, the investment value had a positive influence while labor had no significant influence on the production value. The result also showed that nature of production in agribusiness small industries was labor-intensive which was indicated by the elasticity ccoefficient on the number of workers being grater than the elastiticity coefficient of the investment value. Meanwhile, the nature of production in small non-agribusiness industries was capital-intensive which was shown by the elasticity coefficient on the investment value being grater than the elasticity coefficient of labor. Keywords: Industrial Behavior, Investment Value, Labor and Production Value.